KAMG: A Tool for Converting Blood Ties and Affinity Ties into Adjacency Matrices. Issue 1 (19th July 2016) - Xiong, Hang; Xiong, Pin; Xiong, Hui
Kinship Adjacency Matrix Generator (KAMG) is a browser-based software for creating adjacency matrices using the information of kinship ties. Specifically, it is capable of converting the family trees in the format of GEDCOM files into adjacency matrices of blood relationship. With the data of intermarriages between different families, it can further create the adjacency matrix of affinity relationship for the families. The outcomes can be directly used to create networks. KAMG is written in JavaScript and implemented on web browsers. It is completely open source and the source code is publicly available on GitHub.